DEVELOPMENT OF BASIC COMPETENCIES OF FUTURE RUSSIAN SPEAKERS BASED ON QUALITATIVE APPROACH - Gulmatova Ugilshod Gulmatovna (The Conference Hub, 2025)
This article is devoted to the development of professional competences of future foreign language teachers, in which the strategies of mastering students' reading and writing skills and the characteristics of the competence approach are analyzed. Also, the effectiveness of innovative technologies in the development of professional competencies is revealed.